Exploring Consumers’ Locavorism Through the Lens of Attitude: Empirical Study of Myanmar Market - Atar Thaung Htet (Humanities, Society, and Community, 2024)
As a growing concept of consumer ideology, locavorism is a well-known topic in consumer research. The preference for local food consumption is a crucial issue that is actively discussed at the stage of consumer and sociology research from different perspectives. Therefore, this study explores the locavorism of consumers through the lens of attitudes in Myanmar. There were two specific research objectives in this study: 1) to analyze the effect of locavorism on consumers’ attitudes in the Myanmar market and 2) to examine the effect of attitude on consumers’ purchase intention in the Myanmar market. This study mainly used an explanatory research approach. For data collection, a survey method was employed in this study. For the hypotheses testing, descriptive statistics and multiple linear regression were applied as the major data analysis techniques in this study. According to the result of the empirical analysis, only one of the three attributes of locavorism has a positive and significant effect on attitude. Moreover, attitudes have a positive and significant effect on purchase intentions. Based on the research findings, some major recommendations for both literature and the practical world are made in this study. Among them, local food brands should promote their brand identity by identifying how the consumption of local foods develops the local community economy, as well as in their marketing campaigns. Finally, creating positive attitudes toward local foods that well shape highly intentions to buy local foods because attitudes and purchase intentions are positively related.